Sustainable Formate Production via Highly Active CO2 Hydrogenation Using Porous Organometallic Polymer with Ru-PNP Active Sites - Park, Hongjin; Park, Kwangho; Lee, Ung; Yoon, Sungho (Wiley - V C H Verlag GmbbH & Co., 2025)
Efforts to combine the advantages of homogeneous catalysts in terms of activity with the ease of separation process offered by heterogeneous catalysts continue to be actively pursued in the field of catalyst development. Heterogeneous catalysts were synthesized from Ru-MACHO organometallic compounds, recognized for their high hydrogenation catalytic activity linked to the active site of the Ru-PNP motif, through direct polymerization utilizing the Friedel-Crafts reaction. These catalysts were then applied for the conversion of greenhouse gas carbon dioxide (CO2) into formate via hydrogenation, exhibited with a record-high turnover frequency of 31,700 and a productivity of 36,100 kg(formate)/(kg(catalyst) & sdot; d). Furthermore, the facile separation characteristics and recyclability of the heterogeneous catalysts were confirmed.